PENGENALAN BAHAYA RADIASI DALAM KEHIDUPAN SEHARI - HARI DI SMK KESEHATAN AL FATH SIAK - T.Mohd Yoshandi; Annisa; Yoga Saputra; Dhella Rizkie Gavilla (LPPM Universitas Awal Bros, 2020)
Radiation is a form of energy and heat transfer without transfer medium. These kind of energy and heat transfer found with the sun. Many types of radiation are varied with their spectrum. Radiation Spectrum is depends on its energy and wave length. Radiation with longer wavelength has low energy. The high energy radiation could cause the electron emission within the atomic orbit that called as ionizing radiation. These radiations could give effects to human body such as cancer and fatality. Radiation could be found in the daily life, eg: sun ray, radio wave. Wifi, etc. These radiations are within the safe range spectrum, but any dangerous radiation also could be found exposed the society without realize. Ionizing radiation also could be found in foods such as vegie and fruit that contaminated by radionuclide from mine and factory waste. Ionizing radiation inhaled to human body constantly by radon inhalation that surfaces by the crack of earth crust. The lack of awareness of radiation hazards bring this community services to emerged. The method is by giving lecture to the student of Al Fath Health Focational School in Siak. Lecture delivered with attractive media, games and doorprize, so students could focus more to the lecture given. At the end of the Lecture, the participant given the questioner to evaluate their comprehension of the lecture. The result is objectively the participant comprehend the radiation’s hazard in daily life. After this community service, the Student of Al Fath Health Focational Schoold could comprehend the existence and danger of radiation in everyday’s life.